Adapting and responding to ICTs - a study of two municipalities in rural South Africa - Jacobs, Carl (Department of Information Systems, 2016)
The post - apartheid restructuring of South Africa's water sector has left the responsibility of planning, access and provision of water with local government. Local municipalities, which lack the " financial and human resources to deliver on their constitutional and legal mandate and on citizen expectations" (Department of Co - operative Governance and Traditional Affairs [CoGTA] , 2009) , constitute 71% of South Africa's local government . This means that a large proportion of South Africa's local government does not possess sufficient capacity to fulfil their legal responsibilities. Information and Communication Technologies (ICTs) and the potential for improved capacity they provide is not a new concept, especially to the fields of education, health and governance. For instance, South Africa's Local Government Association (SALGA) developed a guide and roadmap f or successful ICT governance in local municipalities. They recognised the importance of aligning governance and ICTs to improve the role of local municipalities , and while many examples of ICTs successfully improving capacity do exist , there are also many other examples where they failed to do so Literature identifies the reasons for failure and suggests ways to address them so that ICTs have the maximum possible impact on improving capacity , however , many ICTs still fail, especially in developing contexts. This is because most studies in the field of ICTs focus on the impact they have on capacity and not vice versa. Not many studies research the impact that existing capacities have on ICTs, and especially not when the ICTs have already been designed to overcome those challenges usually associated with failure in developing contexts. In view of this, the purpose of this study was to assess what impact rural local municipalities ' existing conditions and capacities have on the implementation and use of ICT s and hence the change in capacity ICTs seek to bring about in the first instance . Additionally, the study assessed whether ICTs bring about any measurable change in low - capacity environments. Two local municipalities in rural Eastern Cape of South Africa , which were looking to improve their capacities to resolve issues of water and sanitation service delivery and maintain customer relations , were identified as the study sites. An ICT system, which sought to address and improve upon the challenges associated with each municipality's customer relations and management of complaints, was co - designed and implemented using best practices, so as to overcome the challenges usually associated with ICT failure in developing contexts. Using the Adaptive Capacity Wheel (Gupta, Termeer, Klostermann, Meijerink, Van den Brink, Jong, Nooteboom, & Bergsma, 2010) , a comprehensive comparative analysis between the pre - and post - ICT implementation capacities of each municipality was undertaken ( both to resolve issues of water and sanitation service delivery , maintain customer relations , and to adapt and respond to the change the ICT system sought to bring about ) . The results showed that the existing conditions and capacities of each municipality did impact the implementation and use of the ICT system. Despite the ICT system being co - designed with the municipalities and their communities to best suit their current conditions, financial and human resource challenges still resulted in each municipality adapting the use of the system to their particular environment. While the adaptations in use benefitted the municipalities, by improving their complaints management and resolution, it negated any benefits the system offered citizens and, as a result, impacted customer relations negatively. The results also showed that ICTs do result in measurable change in low - capacity environments. They are not always the changes expected or designed for, but can, from certain perspectives, end up being the most important. Overall, it is hoped that this study contributes to the discourse of ICT4D implementations in low - capacity environments in relation to the assumption that ICTs inevitably improve capacity. It also highlights the importance of an ongoing debate to rethink the various definitions of ICT for development